INTEREST GROUP SESSION - MEASUREMENT, STATISTICS, AND RESEARCH DESIGN: STRENGTHENING AGING RESEARCH: EXPERIENCES WITH RIGOR, REPRODUCIBILITY, AND TRANSPARENCY. (11th November 2018) - Brown, A W; Allison, D
Abstract: There is renewed interest in rigor, reproducibility, and transparency (RRT) across scientific disciplines, including aging research. For instance, one of the core aims of the Nathan Shock Centers Coordinating Center, the organizer of this symposium that is funded by the Division of Aging Biology of NIA/NIH, is to support RRT. RRT help ensure that evidence used to justify clinical and public health interventions is sound, and strengthen basic science to inform translational efforts. This symposium will address unique challenges and experiences with RRT in four separate, yet overlapping, domains of aging research. We will first discuss general observations regarding statistical and study design issues that affect study validity and causal inference in science in general and aging and gerontological research specifically, reinforcing why the discussion of RRT is timely and important. Next, we will discuss challenges seen in basic science research, from standardizing protocols across sites to unexplained variability and contradictory results despite tight control. We then will describe challenges and opportunities for RRT in large, integrative data analyses using massive amounts of data. The last talk will discuss experiences with designing, executing, and maintaining adherence in trials in aging research, with a focus on heightening rigor while promoting reproducibility and dissemination. Together, these talks will leave the audience with an understanding of the importance of RRT in science in general, help them identify challenges with RRT specifically in aging research, and arm them with tools to mitigate or avoid common errors.